SURGICAL PREVENTION OF PURULENT INGROWN TOENAIL IN CHILDREN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Purulent inflammation caused by ingrown toenails is one of the most common problems in pediatric surgery. This condition can cause significant inconvenience to the child, accompanied by pain, swelling and inflammation, and in more complex cases— purulent discharge. Although in most cases it is possible to manage this disease by conservative methods, sometimes surgical intervention is necessary [9, 6, 4].